Officers And Directors (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
PRESIDENT AND DIRECTOR SCOTT TURNER WASHINGTON, D. C. PAST PRESIDENTS AND DIRECTORS WILLIAM H. BASSETT WATERBURY, CONN. ROBERT E. TALLY JEROME, ARIZ. TREASURER AND DIRECTOR KARL EILERS NEW YORK, N. Y.